Saudi Children Abroad and the Effectiveness of E-Learning (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
Saudi children travel with their parents abroad and enroll in schools and as they interact with foreign cultures, their own native culture will be affected in favor of the dominant culture disconnecting with theirs. Culture, in this case, points to language, religion, and identity of their native country. Once they come back to their native country, the experience is expected to be powerful and allow the individual to grow as well as provide mobility for social action and civic engagement. A Saudi scholar has pointed out that online learning has actually opened up opportunities for Saudi students who are now able to question the traditional methods of education (Alenezi, 2012). With E-learning, students do not have to stay physically in their native countries and not to travel abroad. If they are living abroad, the students can enrol in school in their native country and this will enable them to learn about their culture even away from their home country.The purpose of this research is to review, analyze and investigate children who have been abroad and are not familiar with their native cultures when return. It will attempt to answer the reason why it is important for young children to connect with their culture. The methodology employed questionnaires as a data collection method to express the participants' experiences and perception of e-learning.    Findings in this research revealed that there are many people living abroad who have enrolled their children in schools abroad that do not teach about their native culture. In conclusion, recommendations for more time allocation for the study have and the inclusion of a larger number of people for purpose of data collection. Further research has also been recommended.